The design of a 94 GHz high resolution coherent radar - Celliers, Abraham Francois (Department of Electrical Engineering, 2023)
This thesis describes the design and performance of a 94 GHz short pulse, low duty cycle, high resolution coherent injection locked radar system for sensor applications, with the specific use as an early warning radar ,against high voltage transmission lines. The recent development of solid-state components for frequencies around 94 GHz has made it possible to design coherent millimetre-wave radar systems. Key components of such systems are high power pulsed silicon Impact oscillators, CW Impact oscillators, second harmonic Gunn oscillators, filters, circulators, isolators, couplers, and antennas. Elementary system specifications are derived for the delivery vehicle and the millimetre-wave sensor. Each of the separate components of the system were designed, built, and tested. Measurements were taken with the sensor and are presented. Specific attention is given to the measurement of intra-pulse phase ripple, additive noise, injection locking and coherency. The above-mentioned parameters are critical in the design of a coherent sensor and special care should be given to the various components in the design stage. The sensor is not built into a carrier system yet but was built up as a laboratory model and measurements were taken from the laboratory to various objects and distances outside the laboratory. There is only one article in literature [1] which described a 66 GHz collision warning sensor for helicopters. The system is a noncoherent pulsed radar with the following specifications: